Patients feedback on quality of services and fee proposal in UiTM optometry clinic / Nur Taqiyah Mohamed - Mohamed, Nur Taqiyah (Faculty of Health Sciences, 2015)
The aim of the study was to survey patients’ feedback on the quality of services and correlate quality of services with the fees commensurate offered by UiTM Optometry Clinic. The study also aims to identify which range of fees chosen by the patients after receiving comprehensive eye examinations. Method: One hundred participants who were also patients from Primary Optometry Clinic (POC) UiTM were involved in this study. After finished the eye examinations done by the final year students in POC clinic, patients were asked to fill the survey form given to them. The survey forms were then collected and analyzed. Results: Majority of the participants responded “good” on the quality of services and were highly satisfied with the services provided by the UiTM Optometry Clinic. Though with such good respond on the quality and satisfaction on the services, the fees suggested by the participants was at very low range which was between RM 10 to RM 30. Conclusion: Majority of the participants responded “good” for the quality of services and were “strongly agreed” that they were satisfied on the eye examinations services while the fees recommended by the patients were range from RM 10 to RM 30.